SISTEM PAKAR MENGGUNAKAN METODE FORWARD CHAINING DAN METODE CERTAINTY FACTOR UNTUK MENDIAGNOSA TAHAPAN PENGGUNA NARKOBA - ahmad taufik (Swabumi, 2019)
Drugs have become very real enemies to the present day, not just for people who use these drugs, but also all aspects of constitutional life even to the whole world, because drugs are included in the category of criminal acts that are very dangerous. On the other hand, the perpetrators of drugs also want to return to life like before that are completely separate from the trap of drugs, but they referred to the surrounding environment and the minimal cost of doing media rehabilitation.Therefore, to be able to know the number of drug users, then, the Experts make the concept of an Expert system with Forward Chaining method, Certainty Factor, by using PHP programming language and MySQL database. With this system, Experts are expected to be able to know the level of drug users perceived levels as well as know the possibility of action handling. Keywords: Expert System, Forward Chaining, Certainty Factor, Drugs